Prototype of a selection and acquisition system for libraries - Bontuyan, Hannah M. (2012)
The selection and acquisition process of the library is an essential part of the library. This process is responsible for the building of library collection. Library automations are one way of speeding up the library process but most studies done in library automation focus on cataloging, circulation and OPAC or on the addition of new technologies; and very few studies have focus on the process of the library selection and acquisition. The study aims to answer to the need for an automated system solely dedicated to selection and acquisition. The study also aims to find out the usefulness of the system and determine the features that need to be added or modified. A modified prototyping framework was used in the creation of the system. The prototyping framework consists of five phases which are the identification of the problem, development, evaluation and modification to the prototype. To evaluate the system, a five-point scale questionnaire patterned from the Information Services and Technology Usability Guidelines of the Massachusetts Institute of Technology was used. The evaluation used a summative evaluation approach where 5-7 users were recommended to test the system. The system was evaluated according to its navigation, functionality, user-interface and usefulness. Categories with scores higher that the mean are retained. Some were modified according to the comments and suggestions made by the users. The system received positive results from the users with an overall rating of 4.6 which is above the set standard. The modifications done on the system were then done based on the results obtained from the evaluation.